MODERN CONCEPTS OF DUE TO DYSFUNCTION OF SALIVARY GLANDS - Senchakovich, Y.; Kazakova, E.S.; Yeroshenko, G.A. (World of Medicine and Biology, 2013)
This paper presents an analysis of the causes of hypothyroidism salivary glands and the consequences to which it leads. Found that the secretory activity of the salivary glands play a very important role in the homeostasis and mikrobiotsinoz mouth that affect both dental and somatic health.
Keywords: salivary gland dysfunction; xerostomia